(untitled) (Homoeopathy for All, 2025)
A fundamental change in how homoeopathy must be learnt and experienced by students and teachers is the core of the Competency Based Dynamic Curriculum (CBDC) for BHMS and Entrustable Professional Activities (EPA) for MD (Hom) based curriculum. The logic behind it is very simple, we treat a patient, and a patient represents disruption of his anatomy, physiology, biochemistry, pathology, medicine, surgery when he meets a homoeopath for seeking clinical help. When the patient meets a homoeopath, homoeopath in addition to the above-mentioned knowledge looks back on his tools (Repertory), therapeutic armamentarium at disposal (Materia Medica) and the philosophical stand which he must use to approach the patient to justify the application of the first six aphorisms (Organon). When he sits in his clinic he sits with all this knowledge, skill and attitude he is supposed to have acquired. However, in his post college days, he decides to undergo personal training under someone whom he believes will help establish as a homeopath or learn the hard way by sitting in the clinic or setting up a hospital in which he treats patients becomes competent over a period of time.